Net emission coefficients of low temperature thermal iron-helium plasma - Mościcki, Tomasz; Hoffman, Jacek; Szymański, Zygmunt (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Net emission coefficients of low temperature thermal iron-helium plasma mixture at atmospheric pressure are presented. The calculations are made assuming the plasma is in the local thermodynamic equilibrium at a pressure of 0.1 MPa. The results are presented for several values of helium mass fraction in the mixture (between 0 and 1), for a temperature range 3000 –25000 K and three characteristic plasma dimensions; 0 – corresponding to the optically thin case, and 1 mm and 10 mm. The values of net emission coefficients allow the estimations of total radiation losses in iron-helium plasmas.
Optica Applicata, Vol. 38, 2008, nr 2, s. 365-373
Keywords: optyka; net emission coefficients; iron-helium plasma